Corporate Social Responsibility in Indonesia: A Transformation of Local Wisdom Perspectives - Djufri; Median Wilestari; Molina (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This paper seeks to explore the motivation of management to conduct corporate social responsibility (CSR) activities and disclose it in financial reports from their understanding of local wisdom, using Indonesian companies as a case study. The methodology was carried out through several steps: 1) Survey method by sending questionnaires to selected companies; 2) Content analysis method to determine the scores of CSR disclosures based on the required disclosure standards; 3) Analyzing the results of the company's financial performance to its CSR activities. The empirical evidence proofing that CSR is the transformation of local wisdom into actions and strategies of the company even has not fully become the company's core program. But there are limitations of this study, including the subjectivity of respondents' views concerning the cost of CSR. In addition, it needs to be further clarified because interview (qualitative) data are still very limited. The paper enhances the altruistic attitude shown by the company's management about CSR implementation from their understanding of the local wisdom as a contribution. Therefore, it can be recommended to be a national CSR movement in terms of sustainable development in Indonesia for the next.